Are unexplained adverse health events following HPV vaccination associated with infectious mononucleosis? – A Danish nationwide matched case-control study. Issue 35 (31st July 2020) - Krogsgaard, Lene Wulff; Helmuth, Ida Glode; Bech, Bodil Hammer; Plana-Ripoll, Oleguer; Lützen, Tina Hovgaard; Vestergaard, Hanne Thang; Bjerre, Karsten Dalsgaard; Thomsen, Reimar Wernich; Mølbak, Kåre; Rytter, Dorte
Abstract: Background: In Denmark, the acceptance of the HPV vaccination program has been threatened by reports of suspected adverse events. Epstein Barr Virus (EBV) infection is associated with symptoms of long-lasting tiredness and may be misinterpreted as HPV vaccine adverse events. The main aim of this study was to examine if EBV infection around time of HPV vaccination was a risk factor for later suspected vaccine adverse events. Methods: The study was a nationwide register-based matched case-control study. Cases were females vaccinated against HPV in the period 2011 throughout 2017 with suspected adverse events. For each case, five HPV vaccinated females without suspected adverse events were selected. Information about EBV infection was obtained from the Danish Microbiology Database and assessed for three time periods: (1) before first HPV vaccination, (2) around time of HPV vaccination, and (3) any time during the study period 2010–2017. Multiple logistic regression was used to estimate the association between EBV and suspected adverse events. Results: We identified 1217 cases, matched to 6085 controls. A higher proportion of cases (38; 3.1%) than controls (31; 0.5%) were tested for EBV around time of HPV vaccination and cases had elevated odds for testing both EBV positive (OR 4.52, 95% CI 2.68–7.63) and EBV negative (OR 20.99, 95% CI 5.81–75.79). Only five females were classified with acute/recent EVB infection in this period. Conclusion: Misinterpretation of EBV infection late symptoms is not a leading explanation for Danish females experiencing suspected adverse events after HPV vaccination. Although EBV cannot be excluded as an explanatory factor for a very small proportion of suspected adverse events, the findings are more likely explained by protopathic bias, i.e. the fact that a larger proportion of females suspecting adverse events are tested for EBV.